2017
DOI: 10.1007/s00261-017-1427-6
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon evolutions and complications of common benign liver lesions

Abstract: Frequently encountered on abdominal imaging studies, the majority of common benign liver lesions are asymptomatic, confidently diagnosed by imaging, and do not require further workup, follow-up, or treatment. The increasing use of multimodality liver imaging, has allowed the recognition of uncommon evolutions of common benign liver lesions such as size changes, fibrotic regression, and content and vascularization changes, and their complications such as rupture, hemorrhage, thrombosis, extrinsic compression, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 96 publications
1
12
0
Order By: Relevance
“…Spontaneous hemorrhage and Kasabach-Merritt syndrome are rare [22,23]. In the current study, there was no spontaneous or traumatic intraperitoneal hemorrhage occurred, no recorded Kasabach-Merritt syndrome as it is recorded in children and our cases were adult.…”
supporting
confidence: 41%
“…Spontaneous hemorrhage and Kasabach-Merritt syndrome are rare [22,23]. In the current study, there was no spontaneous or traumatic intraperitoneal hemorrhage occurred, no recorded Kasabach-Merritt syndrome as it is recorded in children and our cases were adult.…”
supporting
confidence: 41%
“…Hepatic hemangiomas are often found incidentally on abdominal ultrasonography (Adriana et al, 2014), and atypical lesions should be further investigated with contrast-enhanced imaging studies such as CT scan and MRI (Satoshi et al, 2009). Abdominal pain and discomfort caused by dilatation of the liver capsule are the most common clinical manifestations of symptomatic hepatic hemangioma, whereas spontaneous hemorrhage and Kasabach-Merritt syndrome are rare, but extremely dangerous (Trotter and Everson 2001;Vernuccio et al, 2018; Kamyab and Rezaei-Kalantari 2019), and the mortality rate of Kasabach-Merritt syndrome has been reported to be up to 40% (O'Rafferty et al 2015). In our study, the majority of patients with hepatic hemangioma are asymptomatic, and most of the lesions were found due to physical examination, other gastrointestinal diseases and abdominal discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have found that estrogen receptors are expressed in hepatic hemangioma and that high estrogen conditions (such as pregnancy and use of oral contraceptives) can promote their growth (Gemer et al 2004;Au and Liu 2005;El-Hashemite et al 2005;Yeh et al 2007b;van Malenstein et al, 2011). Although there have been reports on the natural growth history of hepatic hemangioma, no consensus has been reached (Glinkova et al 2004;Yeh et al 2007a;Hasan et al 2014;Vernuccio et al, 2018). This study investigated the epidemiological characteristics of and the factors affecting the growth of hemangioma, such as age and sex, by analyzing the case data of 534 patients, and hope that our results can provide a theoretical basis for the development of personalized treatment and follow-up programs.…”
Section: Introductionmentioning
confidence: 92%
“…FNH is defined as a nodule composed of benign-appearing hepatocytes occurring in a liver that is otherwise histologically normal or nearly normal [26]. Although FNH may increase in size in 3-15% of cases, these lesions do not evolve to malignancy and their management is conservative [27,28]. FNHs show iso-or hyperintensity in the HBP relatively to liver parenchyma in the vast majority (97%) of cases [10] (Fig.…”
Section: Non-cirrhotic Patientsmentioning
confidence: 99%